2015
DOI: 10.1007/s40257-015-0155-3
|View full text |Cite
|
Sign up to set email alerts
|

Second Primary Malignancies in CTCL Patients from 1992 to 2011: A SEER-Based, Population-Based Study Evaluating Time from CTCL Diagnosis, Age, Sex, Stage, and CD30+ Subtype

Abstract: Occult secondary malignancies, particularly lymphomas, should be considered in adult CTCL patients, including those with the CD30+ subtype.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
50
2
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(57 citation statements)
references
References 16 publications
3
50
2
2
Order By: Relevance
“…Whether discovery of a second primary malignancy within the first year represents a pre‐existing malignancy identified during cancer staging or surveillance remains a controversy and limitation to the study of second primary malignancies. However, while eight patients had a secondary NHL discovered within 1 year of a CTCL diagnosis, 34 were found thereafter, with some latencies greater than 5 years . In the same fashion, Chang et al .…”
Section: Comparison Of the Development Of Second Primary Ctcl In Patimentioning
confidence: 73%
See 2 more Smart Citations
“…Whether discovery of a second primary malignancy within the first year represents a pre‐existing malignancy identified during cancer staging or surveillance remains a controversy and limitation to the study of second primary malignancies. However, while eight patients had a secondary NHL discovered within 1 year of a CTCL diagnosis, 34 were found thereafter, with some latencies greater than 5 years . In the same fashion, Chang et al .…”
Section: Comparison Of the Development Of Second Primary Ctcl In Patimentioning
confidence: 73%
“…In our evaluation of the SEER database between 1991 and 2009, we identified 42 cases of subsequent NHL developing in a cohort of 2923 CTCL patients (1.4%). The results showed a significantly increased risk of NHL in males (SIR, 6.95; 95% Cl, 4.54–10.19) and in females (SIR, 8.24; 95% CI 4.71–13.38) . The development or discovery of a subsequent NHL was highest within the first year of diagnosis of the CTCL.…”
Section: Comparison Of the Development Of Second Primary Ctcl In Patimentioning
confidence: 96%
See 1 more Smart Citation
“…Amber et al [28] confirmed this through examination of the Surveillance, Epidemiology, and End Results (SEER) database of the National Cancer Institute. Through evaluation of all cutaneous T-cell lymphoma cases between 1992 and 2011, there was an overall increased risk of secondary cancers, particularly within the first year of diagnosis [28].…”
Section: Discussionmentioning
confidence: 97%
“…In fact, the combination of rifaximin with partially hydrolyzed GG, a prebiotic that can have a beneficial effect on intestinal motility, seems to be more useful in eradicating SIBO compared with rifaximin alone. 2 Moreover, rifaximin is similar to rifampin which, besides the antibacterial action, has been shown to be a biofilm-dispersing agent. 3 The efficacy of the eradication therapy was evaluated with a new GBT a month later.…”
mentioning
confidence: 99%